PERSPEKTIF AKUNTAN PUBLIK TENTANG KUALITAS LAPORAN KEUANGAN,, INSENTIF BAGI MANAJEMEN,, NILAI ETIS,, DAN PENGENDALIAN INTERNAL DALAM MENYIKAPI PRAKTEK CREATIVE ACCOUNTING - F.X. Kurniawan Tjakrawala; Metta Yuni (Politeknik Negeri Batam, 2017)
The purpose of this study is to obtain the empirical evidences that could predict the causal relationships occured from exogenous constructs such as financial report quality; perceived of management’s incentives; ethical values; and internal control that may influence the endogenous construct, the public accountant’s attitudes towards creative accounting practices. This study used primary data obtained through the field-survey method. The samples of this research subjects were taken by purposive sampling method applied through the distribution of 200 sets of questionnaires. The questionnaires addressed to the respondents who occupied in managerial level of the public accountant companies located at Jakarta, that listed on Indonesian Institute of CPA (IAPI) website and also Financial Service Authority (OJK) of capital market directory. The latent-path modeling applied to analyze the data of 70 units of valid questionnaires (usable response-rate was 35%). The four hypotheses in this study were tested by implementing the technique of Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of hypotheses testing statistically proved able to predict significantly that financial report quality; perceived of management’s incentives; ethical values; and internal control positively influenced the public accountant’s attitudes about creative accounting practices.